Pengaruh Latihan Shooting Menggunakan Target Zona Gawang Terhadap Akurasi Shooting Pemain Futsal Siswa Ekstrakurikuler Sdn 76 Kota Bengkulu - Rahmad Adityo; Feby Elra Perdima; Dolly Apriansyah (UNIVED Press, Universitas Dehasen Bengkulu, 2026)
This study aimed to determine the effect of shooting practice using goal zone targets on the shooting accuracy of student futsal players in the extracurricular program at SD Negeri 76 Bengkulu City. An experimental method with a one-group pretest-posttest design was employed. The study sample consisted of 20 students selected using purposive sampling. The results showed an improvement in the students' shooting accuracy following the intervention; the mean pretest score of 17.90 rose to 30.10 in the posttest. Hypothesis testing yielded a calculated t-value of -21.968 with a significance level of 0.001 (p < 0.05), leading to the conclusion that shooting practice using goal zone targets has a significant effect on improving the students' shooting accuracy. Thus, it is concluded that shooting practice using goal zone targets significantly influences the improvement of shooting accuracy among student futsal players in the SD Negeri 76 Bengkulu City extracurricular program.